I havent done alot of work with these functions... We have been asked to deduce that a particular expression is true. Now, from the data given I have deduced a correct expression, but have been unable to show it is equivalent to the required expression.
My Expression for M: (where n is given)
s = floor(sqrt(n))
A = (n - s(s-1) - s) / s
B = ceiling(A)
M = 2s + B
The required expression for M:
M = ceiling(2*sqrt(n))
As I mentioned, I have been unable to reduce my expression to the required one. Any help would be greatly appriciated!